2014
DOI: 10.15430/jcp.2014.19.4.288
|View full text |Cite
|
Sign up to set email alerts
|

Eugenol-rich Fraction of Syzygium aromaticum (Clove) Reverses Biochemical and Histopathological Changes in Liver Cirrhosis and Inhibits Hepatic Cell Proliferation

Abstract: Background:Dried flower bud of Syzygium aromaticum (clove) is rich in eugenol, an antioxidant and antiinflammatory compound that can protect liver against injury. Clove, besides eugenol, also contains other pharmacologically active phytochemicals such as β-sitosterol and ascorbic acid. This study reports the effect of eugenol-rich fraction (ERF) of clove on liver cirrhosis induced by thioacetamide.Methods:Cirrhosis of the liver, which predisposes to hepatocellular carcinoma, was induced by administering thioac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 60 publications
(68 reference statements)
5
26
0
Order By: Relevance
“…Besides the free radical scavenging activity, eugenol also has nitric oxide scavenging activity, and strong reducing power while determined by Griess reagent and FTC method respectively [6]. Not only the direct free radical scavenging activity in chemical system, eugenol also protected in vitro and in vivo ROS generation and ROS-induced lipidprotein and DNA damage as well as increased the cellular anti-oxidant, specifically, glutathione system ( Figure 3) [3,[17][18][19][20][21]. Wie et al (1997) reported that eugenol reversed neuronal excitotoxic or oxidative injury and had protective effect against N-methyl-D-aspartate-induced neurotoxicity.…”
Section: Antioxidant Activity Of Eugenolmentioning
confidence: 98%
“…Besides the free radical scavenging activity, eugenol also has nitric oxide scavenging activity, and strong reducing power while determined by Griess reagent and FTC method respectively [6]. Not only the direct free radical scavenging activity in chemical system, eugenol also protected in vitro and in vivo ROS generation and ROS-induced lipidprotein and DNA damage as well as increased the cellular anti-oxidant, specifically, glutathione system ( Figure 3) [3,[17][18][19][20][21]. Wie et al (1997) reported that eugenol reversed neuronal excitotoxic or oxidative injury and had protective effect against N-methyl-D-aspartate-induced neurotoxicity.…”
Section: Antioxidant Activity Of Eugenolmentioning
confidence: 98%
“…In this study, we found decrease in the activities of SOD, CAT and glutathione metabolizing GPx with concurrent depletion of GSH on ethanol treatment, indicating the increased oxidative stress which has been implied in the pathogenesis of alcohol-related diseases. Eugenol rich fraction of clove has earlier been reported to mitigate thioacetamide induced liver damage (Ali et al, 2014). Interestingly, Clovinol too could combat the oxidative stress as was evident in significant enhancement of the activities of these enzymes with significant replenishment of the endogenous antioxidant GSH.…”
Section: Discussionmentioning
confidence: 95%
“…Clove buds, rich in polyphenols such as flavonoids, hydrolysable tannins of ellagic acid and gallic acid (Issac et al, 2015) is one of the best antioxidant spice, often referred to as the 'Champion of spices ' (Perez-Jimenez, 2010;Milind, 2011;Shan et al, 2005). Besides, there have been reports on hepatoprotective effects of clove essential oil and clove extracts (Hadary and Ramadan Hassanien, 2015;Al-Okbi et al, 2014;Ali et al, 2014). The present study investigated the efficacy of Clovinol, the polyphenols of clove buds, as a hepatoprotective agent by assessing its effects on liver function markers as well as inflammatory and oxidative stress markers in the rat model for ethanol toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Among these plant the maximum content of eugenol can be obtained from Eugenia caryophyllata, It is the principal source of clove oil which contains 45-90% eugenol as its constituent [1,3,4]. Eugenol, the principal component of Myristica fragrans seed extract is known to have several pharmacological properties [5][6][7][8][9][10]. This versatile bioactive compound is a key ingredient used in the production of perfumes, cosmetics, flavorings agents, culinary purposes and further therapeutically used in the treatment of a toothache.…”
Section: Introductionmentioning
confidence: 99%